THERMODYNAMIC INTERACTIONS AND CHARACTERIZATION OF POLY(ETHYL METHACRYLATE) BY INVERSE GAS-CHROMATOGRAPHY - KAYA, I; OZDEMIR, E (Marcel Dekker Inc, 1995)
The inverse gas chromatography (i.g.c.)method was applied to poly(ethyl methacrylate) (PEMA)as a method for polymer characterization and thermodynamic interactions. We have shown that the method was useful in obtaining meaningful thermodynamic data on PEMA-solvent systems. Five different families with different chemical nature and polarity were used to obtain some insights about PEMA-solvent interactions. PEMA was found to decompose above 210 degrees C (determined by TGA). The PEMA-solvent interaction parameters and the free energy of mixing mere determined at a series of temperature. The glass transition temperature (Tg), of PEMA was found about 70 degrees C. The thermodynamic sorption functions for the sorption process of the different chemical nature of probes into PEMA solution were obtained and discussed in terms of their interactions with PEMA. Furthermore, the contributions of CH2.C= O.C= O- OR,aromatic and OH functional groups in the five series to the sorption process were also obtained. We found that the formation of hydrogen bond between the C= O group of PEMA and the OK group of the alcohol is stronger than the dipole-dipole interactions between PEMA and the carbonyl groups of at the acetate and ketone and the dispersive forces between PEMA and the alkanes. Acetates and ketones mere found to be good solvents and weak solvents respectively PEMA Alkanes, o-xylene and methanol mere found to be non-solvents of PEMA.
Keywords: Glass-Transition Temperature; Poly(Vinylidene Fluoride); Blends; Dependence; Polymers; Behavior